La Inulina como fuente de fibra alimentaria y su relación con la salud humana - Arango Bedoya, Oscar; Hurtado B., Andrés Mauricio; Osorio M, Oswaldo (Universidad y Salud, 2009)
Inulin is undigested oligosaccharide with demonstrable effects on health. Many studies have shown that inulin reduces the risk of arteriosclerosis and increases the bioavailability of several minerals. It also reduces the risk of gastrointestinal diseases and lowers levels of cholesterol and triglycerides in the serum. Besides, it controls the levels of glucose in blood, reduces the liberation of toxins and carcinogens, and stimulates the immune system. These effects allows inulin to be considered as functional food, along with the ability to add texture and improve rheological characteristics and nutritional properties of food. This bibliographic review presents the concepts of dietary fiber concepts, inulin characteristics and sources, its technological functionality and use in the industrial food, and detailed description about its beneficial effects on human health.